Clinico epidemiological and mycological study of pityriasis versicolor PITYRIASIS VERSICOLOR - Snekavalli, R.; Madhu, R.; Ramesh, A.; Janaki, C.; Dhanalakshmi, U. R. (International Journal of Research in Medical Sciences, 2018)
Background: Pityriasis versicolor, a chronic superficial fungal infection caused by lipophilic yeasts of the genus, Malassezia is a common infection in the tropical and subtropical regions. Objective was to study the epidemiology, clinical presentation, associations, etiological agents and clinico-mycological correlation of pityriasis versicolor. Methods: Hundred patients with clinical diagnosis of pityriasis versicolor who attended the mycology out-patient (OP) clinic between September 2014 and August 2015 were enrolled. Skin scrapings from these patients were subjected to 10% potassium hydroxide (KOH) and culture. Results: Out of the 100 patients with pityriasis versicolor (PV), 70% were males and 30% were females and the most affected age group was between 21-30 years (43%). The youngest age affected was a 13 years old male while the oldest was a 65 years old male. Duration of the infection ranged between 1 month to 6 months in 65% while it was more than 1 year in 9% of patients. Recurrence was observed in 35% of them. Back was the most common site (48%) to be involved. Seventy percent of patients had more than 30% body surface area involvement. Achromic type of PV was the most common clinical presentation in 68% of patients. Out of the 76 isolates, Malassezia globosa was the predominant isolate (48.7%), followed by M. sympodialis (25%), M. furfur (10.5%), M. restricta (7.9%) and M. obtusa (6.6%). Conclusions: Achromic type of PV is the most common clinical presentation. Malassezia globosa is the most common etiological agent of pityriasis versicolor.